2017
DOI: 10.1371/journal.pone.0171692
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analysis of agronomic traits in wheat under drought-stressed and non-stressed conditions

Abstract: This study determined the population structure and genome-wide marker-trait association of agronomic traits of wheat for drought-tolerance breeding. Ninety-three diverse bread wheat genotypes were genotyped using the Diversity Arrays Technology sequencing (DArTseq) protocol. The number of days-to-heading (DTH), number of days-to-maturity (DTM), plant height (PHT), spike length (SPL), number of kernels per spike (KPS), thousand kernel weight (TKW) and grain yield (GYLD), assessed under drought-stressed and non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
100
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(130 citation statements)
references
References 44 publications
28
100
0
2
Order By: Relevance
“…This is not surprising given the low polymorphism rate and PIC values in groundnut which means that detectable recombination is likely to be very low. Several studies have reported LD decay with distance [10,38,39] which agrees with the findings of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…This is not surprising given the low polymorphism rate and PIC values in groundnut which means that detectable recombination is likely to be very low. Several studies have reported LD decay with distance [10,38,39] which agrees with the findings of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Phenotypic datasets for association mapping included BLUP trait values across geographic regions (Asia, Africa, North America, and by individual countries) and by growing season (2010 and 2011) and BLUE calculated for each individual environment (see Supplemental Table S2 for the complete description of the datasets used for GWAS). A P value of < 0.001 was used as the threshold for defining significant SNP as the measured traits have generally low to moderate heritability (Arguello et al, 2016; Mwadzingeni et al, 2017) and due to the observed deviations on the quantile‐quantile plots. Polymorphic SNPs for the winter wheat loci were separated according to allele calls, and the mean GY for these were compared using t test at P < 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…The development of drought-tolerant genotypes as well as genotypes with higher water-use efficiency (WUE) is of global interest due to a rapid decrease in water resources destined to agriculture (Araus et al 2008). A large number of morphological and physiological traits have been found to be linked to drought tolerance in cereals (Condon et al 2004;Reynolds et al 2005;Araus et al 2008;Mora et al 2015;Mwadzingeni et al 2017).…”
Section: Discussionmentioning
confidence: 99%